1975
DOI: 10.1056/nejm197509252931303
|View full text |Cite
|
Sign up to set email alerts
|

Defect in Pyridine Nucleotide Dependent Superoxide Production by a Particulate Fraction from the Granulocytes of Patients with Chronic Granulomatous Disease

Abstract: Particulate fractions from normal human granulocytes preactivated with opsonized zymosan were found to catalyze superoxide production in the presence of reduced pyridine nucleotides. Similar preparations from three patients with X-linked chronic granulomatous disease produced no detectable superoxide. The failure to produce superoxide was not due to an inhibitor, since cell-free preparations from the patients' granulocytes had no effect on superoxide production by normal particles. Particles from the mothers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0
1

Year Published

1976
1976
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(49 citation statements)
references
References 29 publications
2
46
0
1
Order By: Relevance
“…This suggests that superoxide is involved even in the enzymatic oxidation of NADPH by isolated granules. These results agree with those reported by Patriarca et al (8) in guinea pig cells and are also consistent withl observations by Curnutte et al (18), that NADPHdependent superoxide production occurred in a 27,000 g granule fraction from human PMNL. An alternate interpretation of our results is that enough manganese ion is present in the granule fraction to cause, in combination withl superoxide.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…This suggests that superoxide is involved even in the enzymatic oxidation of NADPH by isolated granules. These results agree with those reported by Patriarca et al (8) in guinea pig cells and are also consistent withl observations by Curnutte et al (18), that NADPHdependent superoxide production occurred in a 27,000 g granule fraction from human PMNL. An alternate interpretation of our results is that enough manganese ion is present in the granule fraction to cause, in combination withl superoxide.…”
Section: Resultssupporting
confidence: 94%
“…A possible explanation for the difference is that Paul's group studied guinea pig cells, while our studies and those of Patriarca utilized human cells. This hypothesis is further weakened by the presence of normal NADPH oxidase activity in the PMNL of patients deficient in myeloperoxidase (3,18).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they failed to detect this increase in cell homogenates. As it currently stands, this also questions previous reports on NADPH oxidase activity in membrane fractions from neutrophils [91] and even discredits the original assays described by Babior and colleagues using cytochrome c reduction for superoxide detection in these particulate fractions or homogenates [93,94] and subsequent studies. By experiments in HEK293 cells overexpressing Nox4, Nox5, eNOS and P450 2C8 they finally identified eNOS as the most likely candidate for generating the NADPH-triggered lucigenin ECL signal in intact cells and their membrane fractions [105], although previously the eNOS inhibitor L-NNA had no effect on the superoxide signal generated by NADPH in membrane fractions [102].…”
Section: Nadph Oxidase Activity Assays In Isolated Membrane Preparatimentioning
confidence: 85%
“…Lucigenin ECL is also used for two decades to detect superoxide formation from NADPH oxidase in membrane fractions of aortic tissues [89,90] and even longer, since 1984, in particulate fractions of activated neutrophils [91]. After the initial discovery of superoxide producing NADPH oxidase in isolated leukocytes (oxidative burst) by Babior and colleagues (measured by cytochrome c reduction which was blocked by superoxide dismutase) [92], the same authors reported on a vital oxidative burst from particulate fractions (27,000 g preparations) from homogenates of zymosan-activated human neutrophils in the presence of NADPH (measured by cytochrome c reduction, prevented by superoxide dismutase), which was absent in particulate fractions from neutrophils from patients with chronic granulomatous disease [93,94]. Later it was shown that translocation of the Nox subunits p47 phox and p67 phox from the cytosol to the membrane is an essential step for detection of NADPH-triggered superoxide formation by particulate fractions of phorbol ester-stimulated human neutrophils, which again was absent in neutrophils from patients with chronic granulomatous disease [95], a process that is accompanied by Rac-2 translocation from the cytosol to the membrane [96].…”
Section: Nadph Oxidase Activity Assays In Isolated Membrane Preparatimentioning
confidence: 99%